2009
DOI: 10.1080/17470910802319710
|View full text |Cite
|
Sign up to set email alerts
|

Sharing secrets: Oxytocin and trust in schizophrenia

Abstract: Previous studies indicated that oxytocin plays an important role in human trust, which is impaired in patients with severe mental disorders. In this study, we measured plasma oxytocin levels in patients with schizophrenia (n=50) and in healthy controls (n=50) after neutral and trust-related interpersonal interactions. Trust-related interactions were associated with increased oxytocin levels in controls. This effect was absent in patients with schizophrenia. Low oxytocin levels measured after trust-related inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 34 publications
6
113
0
Order By: Relevance
“…Cognitive deficits are a prominent and disabling component of schizophrenia, and the efficacy of current pharmacologic treatments is limited. Plasma OT concentrations are lower in schizophrenic patients than in normal subjects and negatively correlate with psychotic symptoms (69,70). The first evidence of the beneficial effect of OT on memory comes from a small group of schizophrenic patients treated with intranasal OT (20 IU) twice a day for 1 week and then with 40 IU twice a day for a further 2 weeks (71), who showed a striking improvement in short-term but not long-term verbal memory as assessed by the California Verbal Learning Test and the Letter Number Sequence.…”
Section: Human Studiesmentioning
confidence: 97%
“…Cognitive deficits are a prominent and disabling component of schizophrenia, and the efficacy of current pharmacologic treatments is limited. Plasma OT concentrations are lower in schizophrenic patients than in normal subjects and negatively correlate with psychotic symptoms (69,70). The first evidence of the beneficial effect of OT on memory comes from a small group of schizophrenic patients treated with intranasal OT (20 IU) twice a day for 1 week and then with 40 IU twice a day for a further 2 weeks (71), who showed a striking improvement in short-term but not long-term verbal memory as assessed by the California Verbal Learning Test and the Letter Number Sequence.…”
Section: Human Studiesmentioning
confidence: 97%
“…A key player in the detection of relevant stimuli in our environment, including our response to apparent threat, is the amygdala, which is activated by excitatory pathways that connect the central amygdala nucleus to the midbrain, and thence to the autonomic nervous system. Excessive amygdala activation during social encounters raises anxiety, leading to social withdrawal (18). In humans, such activation is potently increased by direct eye contact (19,20).…”
Section: Ot Social Recognition and The Response To Threatmentioning
confidence: 99%
“…In contrast, Goldman and colleagues showed that blunted OT levels in schizophrenia were associated with low performance in a facial affect rating task [53]. Another study investigating the effect of a trust-related interaction on peripheral OT levels revealed that schizophrenic patients lacked the interaction-induced increase in peripheral OT observed in healthy controls [88]. Not only OT but also AVP functioning was found to be abnormal based on the investigation of neurophysin immunoreactivity in different brain areas [108].…”
Section: Schizophreniamentioning
confidence: 99%